Depression of muscle and cutaneous afferent-evoked monosynaptic field potentials during fictive locomotion in the cat - Perreault, M-C (Blackwell Science Inc, 1999)
1. Monosynaptic extracellular field potentials evoked by electrical stimulation of ipsilateral hindlimb nerves carrying muscle group I, II and cutaneous afferents were examined during fictive locomotion. Fifty-eight field potentials were recorded in the dorsal and intermediate laminae throughout the mid-lumbar to first sacral segments and fictive locomotion was evoked by mesencephalic locomotor region (MLR) stimulation in paralysed decerebrate cats. 2. The majority (96 %) of group I, II and cutaneous-evoked field potentials were decreased during fictive locomotion. Group I, cutaneous and dorsal group II potentials were reduced on average to about 80 % of control values. Group II field potentials recorded in the intermediate laminae were reduced to a mean of 49 % of control values. Cyclic variations in field potential amplitude between the flexion and extension phases were observed in 24 of 45 cases analysed. Of those 24 field potentials, the two group I and four cutaneous field potentials were smaller during the flexion phase. All eleven group II and the remaining seven cutaneous fields were smaller during extension. In all but two cases, these cyclic variations were smaller than the tonic depression upon which they were superimposed. 3. In 7/9 group II field potentials examined, reductions (on average to 85 % of control) began with the onset of MLR stimulation that produced tonic activity in the motor nerves before the onset of rhythmic alternating, locomotor discharges. In six of the seven cases the field potential depression increased with the establishment of fictive locomotion. This observation and the cyclic modulation of field potentials during fictive locomotion suggests that the depression was strongly linked to the operation of the spinal locomotor circuitry. 4. Depression of the monosynaptic components of the field potentials suggests a reduction in synaptic transmission from primary afferents to first-order spinal interneurones during fictive locomotion. Accordingly, the larger depression of intermediate group II field potentials may indicate a preferential reduction in transmission from group II afferents to interneurones located in intermediate spinal laminae. 5. Flexion reflexes evoked by group II and cutaneous afferents were also depressed during MLR-evoked fictive locomotion. The possibility that this depression results from a reduction in transmission from primary afferents, and in particular from group II afferents, ending on interneurones in the intermediate laminae is discussed.